Anti-seizures therapeutics in patients with epilepsy: an approach to levetiracetam – review - Rusinowska, Barbara (Journal of Education, Health and Sport, 2022)
Epilepsy is a chronic condition that consists of a transient disorder of brain function manifested by recurrent and unprovoked seizures affecting approximately 50 million people worldwide. Antiepileptic treatment is aimed at possible improvement the quality of life by reducing epilepsy seizures with the lowest possible side effects. One of the newest broad spectrum antiepileptic drug (AED) for the treatment of wide range of epilepsies – focal, partial, myoclonic, tonic-clonic and primary generalized seizures that can be used in both children and adults is levetiracetam. Levetiracetam is believed to bind to SV2A (synaptic vesicle protein 2A) in the brain, prevent the release of calcium stores from neurons and inhibit GABA and glycine activity. Due to the unique mechanism of action, high bioavailability (in both oral and intravenous administration), rapid absorption, metabolism based on the hydrolysis of acetamide groups in the blood (independent of the liver) and the lack of activity of the resulting metabolites, the drug is considered to be safe and effective in reducing and stopping seizures. In this review, we present the latest reports on the effectiveness of levetiracetam and its potential in the treatment of epilepsy in children and adults.